The Rhetoric of Reconciliation - Sobczak, Barbara (My University, 2013)
This article examines the functioning of rhetoric in public discourse, in particular a rhetoric that emphasizes the importance of reaching accommodation with people and consensus building, called the rhetoric of reconciliation. The conditions for the rhetoric of reconciliation include: 1) a given rhetorical situation that consist of an issue, a conflict situation that can be either viewed as something that has existed for ever and therefore underlies the sources of any relation, or is treated as only a stage in the history of a relation that occurred after a time of agreement and unity; 2) the opening to dialogue that requires primarily self-definition, a definition of one’s identity, demarcating boundaries and then, acknowledging the individuality (uniqueness) of the Other, 3) the language of empathy for reducing the degree of defensiveness in reaching an agreement; 4) the ethos of the speaker, based on knowledge, friendliness and openness. An important element of the rhetoric of reconciliation is opening gestures, i.e., such signs and conduct, both verbal and non-verbal, that express a readiness and willingness to dialogue and understanding. However, the rhetoric of reconciliation should be distinguished from the “empty” rhetoric (sophistry) that restricts itself to making gestures only. The difference between them relates to intention – the standing and the attitude of the rhetor, ethical issues and goals to be attained. The “empty” rhetoric suits only immediate and spectacular gestures of reconciliation of expedient nature, whereas the rhetoric of reconciliation undertakes efforts that will last for years or even decades.
Keywords: dispute; rhetoric; reconciliation; dialogue; the language of empathy; persuasion; public discourse; conflict